Improving MIMO radar's performance through receivers' positioning. Issue 5 (1st July 2017) - Chitgarha, Mohammad Mahdi; Radmard, Mojtaba; Nazari Majd, Mohammad; Nayebi, Mohammad Mahdi
Abstract : By employing the MIMO (multiple‐input–multiple‐output) technology in radar, some new problems emerged, that, in order to benefit the MIMO gains in radar, it was necessary to solve them suitably. One of such obstacles is determining the positions of receive antennas in a MIMO radar system with widely separated antennas (WS MIMO radar), since it is shown that the antennas' positions affect the whole system's performance considerably. In this study, a proper receivers' positioning procedure is proposed. To do this end, four criteria are developed based on the proposed MIMO detector and the MIMO ambiguity function. The simulations verify that the proposed positioning procedure improves the radar's performance in many aspects, such as the overall probability of detection.